Outcomes of Wound Healing after Plasma-Rich Platelet Therapy - Juwereya Memon; Sana Mughal; Sumair Memon; Raima Kalhoro; Uzma Qureshi (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To identify outcomes of wound healing after using Plasma Rich platelet therapy. METHODOLOGY: A prospective cross-sectional study was conducted at ISRA University Hospital, Hyderabad, from July to December 2022, with a sample size of 50 and a non-probability sampling technique. Both genders aged 45 to 75 years, Diabetes mellitus type II, Chronic or Non-healing wounds/ulcers for 3 to 6 months, and Wound size 2cm to 6cm were included. Participants who were not willing to study, Patients on steroid and Anticoagulant therapy and Immunosuppressive drugs, Pregnant females, those with Cardiovascular Disorders, and Associated Lymphoedema were excluded. Data was analyzed by SPSS version 21. RESULTS: Fifty patients were enrolled after matching the inclusion and exclusion criteria. The age range was 40 years to 70 years. Thirty-one were males, and 19 were females. Co-morbid conditions included were diabetes mellitus type II and hypertension. The most common cause of lower limb ulcers was diabetic foot, and the most common site was the dorsum of the foot. 52% of patients had <2cm size ulcers, and they responded well to plasma-rich platelet therapy in a single session. PRP is a cost-effective, advanced therapy and safe procedure to manage wound healing. It improves quality of life, reduces hospitalization, and decreases hospital visits, which would lessen the patient burden. It works on cellular regeneration, so it helps in faster recovery and avoidance of old traditional methods and excessive or misuse of antibiotics. CONCLUSION: Plasma Rich Platelet therapy is a safe method for treating chronic and non-healing ulcers.